ALLIGNMENT STRATEGIC MODEL AND CHANGE MANAJEMEN IN HIGHER EDUCATION BASED ON ELECTRONIC SYSTEM (Studycase Private Colleges In Indonesia) - Anuar Sanusi; Linda Septarina (Saburai International Journal of Social Sciences and Development, 2018)
The change management in higher education governance is able to adapt into a global change of businesses and sustainable technologies. This study aims to assess the empowerment profile-based on the change management governance quality. This research uses quantitative method to collecting data and documentation by triangulation technique to determine the main factors of quality policy, mechanism of reference preparation theory to fit theoretical reference and quality guarantee. The results show that there are changes of quality based on the governance management because of the main factor or the quality target indicators.Hopely this research can give theorytical and practice contribution,and to examine the previous theory about change management, strategic relevancy and empowerment model through higher education performance improvement to reach excellent competitive of higer education. On the other hand,practically this research can measure how far the model can increase alligment strategic in improving empowerment of higher education by utilizing of using information system resources.